The agriculture: An indicator for the rural development in Maramures County - Ioan Niculae Alecu; Talida Giambaşu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
Romania's rural development and, implicitly, of Maramures county is a sector of significant importance, which has become a priority also for the European Union, particularly since 91% of the European territory is represented by rural areas. In Maramures County, the rural environment is faced with a set of important issues that require urgent settlement in order to fulfil the desire for sustainable development. The purpose of this work is to identify, by analyzing the current data provided by the National Statistics Institute, the main weaknesses in this sector and the potential rehabilitation opportunities. The results of the survey can be successfully corroborated with other surveys of other rural development indicators, so that a clear and accurate image of the current status can be outlined, upon which actual strategies of relaunching certain sectors can be conceived, in order to raise the quality of rural life and to achieve the objectives of sustainable rural development, by connecting the actions to the needs.
Keywords: 330; rural development; zootechnics; agriculture; Maramures